One-year outcomes following primary stenting of infrapopliteal steno-occlusive arterial disease using a non-polymer sirolimus-eluting stent: Results from a prospective single-centre cohort study - Tigkiropoulos, Konstantinos; Lazaridis, Ioannis; Nikas, Spyridon; Abatzis-Papadopoulos, Manolis; Sidiropoulou, Katerina; Stavridis, Kyriakos; Karamanos, Dimitrios; Saratzis, Athanasios; Saratzis, Nikolaos (Frontiers in Surgery, 2022)
Background: Clinical outcomes using new generation drug-eluting stents designed specifically for infrapopliteal disease are not widely available, especially in comparison to paclitaxel-based therapies. This series reports one-year outcomes in patients with diabetes and chronic limb threatening ischaemia (CLTI) undergoing angioplasty with a sirolimus-eluting tibial stent evaluating feasibility ,safety and efficacy of this new device (Cre8, Alvimedica, Turkey). Outcomes were compared to matched patients undergoing infrapopliteal angioplasty using a paclitaxel-coated balloon (DCB). Patients and Methods: Patients with diabetes and CLTI requiring infrapopliteal intervention were recruited prospectively to undergo angioplasty and primary stenting using the Cre8 sirolimus-eluting stent (DES) between January 2018 - October 2020; outcomes were compared to a group of patients with diabetes and CLTI who had undergone infrapopliteal angioplasty using a DCB. All patients were followed-up for at least 12 months using a uniform protocol with duplex ultrasound and examination. The primary outcome measure was target lesion patency (<50% restenosis). Clinically driven target lesion revascularisation (CD-TLR), amputations, Rutherford stage, and mortality were also recorded. Results: 54 patients (61 target lesions; median age: 69 years, 74% male) were included [27 with the Cre8 device (main group) vs. 27 with a DCB (historical controls)]. Primary patency at 12 months was 81% in the Cre8 group vs. 71% in the control group (p=0.498). Overall, 4 (15%) patients in the Cre8 group vs. 3 (11%) patients in the control group underwent a major amputation within 12 months (p=1.0). CD-TLR (all endovascular) did not differ between groups at 12 months (4% Cre8 vs. 10% control group, p= 0.599). Rutherford stage improvement at 12 months was superior for the Cre8 group (52% vs. 15% improved by at least one stage, p=0.039). One year mortality was 15% in the Cre8 group vs. 22% in the control group, p=0.726. Conclusions: Primary stenting with the Cre8 stent is feasible and safe in diabetic patients and CLTI. When compared to patients undergoing angioplasty with a DCB, there were no significant differences regarding primary patency, CD-TLR, major amputations, and mortality at 12 months. Those treated with a Cre8 stent were more likely to have an improvement in their Rutherford stage.